2008
DOI: 10.1007/s00122-008-0720-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Na+ and K+ concentrations in leaf and stem as physiological components of salt tolerance in Tomato

Abstract: The sodium and potassium concentrations in leaf and stem have been genetically studied as physiological components of the vegetative and reproductive development in two populations of F(8) lines, derived from a salt sensitive genotype of Solanum lycopersicum cv. Cerasiforme, as female parent, and two salt tolerant lines, as male parents, from S. pimpinellifolium, the P population (142 lines), and S. cheesmaniae, the C population (116 lines). Genetic parameters of ten traits under salinity and five of them unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 52 publications
(61 reference statements)
3
98
1
1
Order By: Relevance
“…Based on QTL analysis of physiological and yield traits of two segregating populations derived from a salt-sensitive S. lycopersicum var. cerasiforme genotype and one salt-tolerant male line each of S. pimpinellifolium and S. cheesmaniae, Villalta et al (2008) observed that fruit yield was not strongly associated with any physiological or vegetative trait under salinity. Only two sodium QTLs could be mapped in genomic regions of chromosome C1 and C8 where fruit yield QTLs were also located, but in both cases the beneficial allele corresponded to the salt-sensitive, cultivated S. lycopersicum var.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on QTL analysis of physiological and yield traits of two segregating populations derived from a salt-sensitive S. lycopersicum var. cerasiforme genotype and one salt-tolerant male line each of S. pimpinellifolium and S. cheesmaniae, Villalta et al (2008) observed that fruit yield was not strongly associated with any physiological or vegetative trait under salinity. Only two sodium QTLs could be mapped in genomic regions of chromosome C1 and C8 where fruit yield QTLs were also located, but in both cases the beneficial allele corresponded to the salt-sensitive, cultivated S. lycopersicum var.…”
Section: Discussionmentioning
confidence: 84%
“…Salt tolerance traits have been introgressed successfully into commercial tomato varieties from the wild tomato species S. cheesmaniae and S. pennellii through backcrossing or recurrent selection methods (Shannon 1997). Although S. pimpinellifolium is the closest relative of cultivated tomato and several accessions already have been identified and characterized for salt tolerance (Bolarín et al 1991;Cuartero et al 1992;Hassan et al 1990;Villalta et al 2008) the use of this species in breeding programs for salt tolerance is still largely untapped. Salt tolerance of crops is often expressed as relative yield depression for a defined level of soluble salts in the soil solution compared with yields under nonsaline conditions (Bernstein et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…However previous studies have as well identified a non-significant correlation of Na ? accumulation with salt stress tolerance in tomato (Rao et al 2013;Villalta et al 2008). In fact, Na ?…”
Section: Discussionmentioning
confidence: 99%
“…Marker-assisted selection (MAS) based on QTL analysis can greatly facilitate crop improvement (Tuberosa and Salvi 2007). Many QTLs for salt tolerance have already been detected in barley (Hordeum vulgare L.) (Mano and Takeda 1997), rice (Oryza sativa L.) (Gong et al 1999;Lee et al 2006;Lin et al 2004;Prasad et al 2000;Takehisa et al 2004), tomato (Solanum lycopersicum L.) (Foolad 1999;Foolad and Chen 1999;Foolad et al 2001;Villalta et al 2008) and arabidopsis (Arabidopsis thaliana L.) (Quesada et al 2002).…”
Section: Introductionmentioning
confidence: 97%